Estratégias de renovação da telenovela: a produção de uma estética da diferença em Cordel Encantado - Aires, Aliana Barbosa (2013)
The contemporary consumer society has novelty and experimentation in its flagship brand, which sets a transience economy that is based on ceaseless production of objects to boost consumption practices. The theme of this research is the brazilian telenovela renewal strategies, from a logics production study of Cordel Encantado telenovela constituting the corpus of our analysis. The research problem on which we stop is to figure out which strategies were mobilized to produce an aesthetic difference at Cordel Encantado and how they promote a telenovela renewal. For this, we investigate the ruptures and discontinuities in brazilian telenovela format, considering those productions that presented new level of narrative, language television and theme. In the contemporary audiovisual landscape Cordel Encantado was considered the highlight of the year 2011 by Obitel Yearbook "With a different proposal in terms of thematic approach and aesthetic finish" (lopes at al, 2012, p. 158).Thus, we sought in this study to characterize an "aesthetic difference" as a differential producer of this telenovela from the "aesthetic of repetition" which is proper from the format. We identify the marks of poetic project that directed Cordel Encantado and verify the negotiation processes of meaning in this production. Leading us by the concepts of residual, emergent and dominant, proposed by Williams (1979) in Marxism and Literature, we classify production resources mobilized in Cordel Encantado aligning them to these categories. As for the results, we can say that there is an "aesthetic difference" in Cordel Encantado, made possible by repetition and articulation of specific dominant, residual and emergent elements. The dominant element is represented in the characteristics of the most popular brazilian television format, telenovela, whose main genre is the melodrama, and is guided by na aesthetic realistic model. The reference to the literature of Cordel, to fairy tales and medieval myths represents the residual elements used in the production of Cordel Encantado, and emerging occurs through the northeast thematic under a standpoint playful, and by building a renewed aesthetic language by using the technique of 24 frames, a feature film that was brought first to a telenovela.